Present day school readers in rapport with the dramatic works of a once-banned Albanian author - Shingjergji, Besa; Ciftja, Hektor (Journal of Education Culture and Society, 2020)
The process of reading, rereading, scrutinizing, re-scrutinizing and appraising an author’s work is not fi nite; moreover it is very dynamic and full of suprises. No doubt that the appraisal and re-appraisal is too complex, including cultural, literary, gender and genre components. This becomes more obvious when referring to an author whose works had been locked up in library stacks during the whole 45 years of totalitarian rule in Albania, and whose appraisal process cannot help facing up to the critical thinking led by biased politicization. In this study the appraisal of the works of one of the most outstanding Albanian writers of the 30s of the twentieth century, Etëhem Haxhiademi, will be done by presenting them in rapport with the present-day school, pre-university and university level readers. This re-appraisal is conducted with a cold logic, devoid of the vindictive political principles which brought the distorted evaluation of the authors’ works, as it happened for many other au-thors as well, and is striving to place the writer into the system of the genuine literary values. Once the reader’s inquisitiveness has been satisfi ed, even after reading a less-known or, moreover, an oblivious or banned literary work, he/she begins reading and rereading it, looking closely into it, essaying to fi nd a proper place for this work in the general system of the national, inter-balkanic and international literary values.E. Haxhiademi’s literary work was known by an older generations of readers whose es-thetic satisfaction it brought forth was confi ned in their consciousness: it was unknown or partly known, not by direct reading but by several interpretations of others, by a middle generation of readers who displayed a certain artistic uncertainty and indifference. However, nowadays it is intently being studied although in excessively fragmentary ways and in many cases even unsuitable ones, by the younger generation of readers who should have a more motivated curiosity for divulging its real values.In the history of the Albanian literature, as well as in the other East European Countries, the authors’ biographies and especially their political aspects, were used as selective criteria to appraise authors and their works, instead of being pure cognitive and studying means. This study intends to reveal the present-day school readers’ affi rmative attitudes or even the non-affi rmative ones, regarding Haxhiademi’s literary works, in the process of re-dimen-sioning the author’s values and those of his literary works.